High uniaxial buckling strain for measuring the mechanical properties of nanoporous gold films. (May 2021) - Lee, Jaeseon; Park, Jieun; Yoo, Dayoung; Zhang, Mao; Choi, Changsoon; Kim, Yangdo; Hong, Suck Won; Lee, Dongyun
Abstract: Excellent studies have been conducted to understand the mechanical behavior of thin films by buckling the films using heat-shrinkable substrates. A buckling-based method [Stafford et al., Nat. Mater. 3 (2004) 545] has been adopted to measure the mechanical properties of nanoporous gold (NPG) films. This method is highly suitable under low-strain conditions; however, we attempted to use this approach under high-strain conditions. The calculated (8.2 GPa) and measured (10 ± 1.3 GPa) values of Young's modulus are remarkably near the literature value (8.8 GPa). Owing to the high-strain conditions, the effects of pore size on the Young's modulus [J. Erlebacher, J. Mathur, Appl. Phys. Lett. 90 (2007) 061910] may not be considered, and the cracks and delamination of the NPG films from the shrunken substrate were considered to interpret the mechanical behavior of the films. Graphical abstract: Image, graphical abstract